Pengenalan Software Office Menggunakan Microsoft Office Di SMPN 14 Depok - Nandi Adi Nugroho; Adrian Chandra Kusumah; Genta Aldora Leopriandis; Achmad Khautsar Rizaldi; Kezia Maruenci (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance students’ digital competencies by providing training on the use of social media as a primary platform for digital branding. The activity was carried out at SMKN 04 Kota Tangerang and involved students as active participants. The training materials covered brand identity, content planning, and the importance of visual consistency in building a strong digital presence. The sessions emphasized hands-on practice and interactive participation, particularly in content creation for social media platforms. The training effectively improved students’ understanding and skills in managing social media with a more strategic and creative approach. Participants were able to design content tailored to their target audience and utilize social media as an efficient promotional tool. Despite technical challenges such as limited devices and internet access, these obstacles were managed through schedule adjustments and support from the school. This program provided a valuable contribution to preparing students for digital-era challenges and opened opportunities for independent entrepreneurship. To ensure sustainable impact, similar training sessions are recommended to be held regularly, supported by adequate facilities and post-training online discussion forums. Continuous involvement from schools, government agencies, and the private sector is essential to strengthen the competitiveness of the younger generation in the evolving digital ecosystem.